Binder composition, binder, preparation method of binder and negative plate

By using carboxymethylated tamarind polysaccharide gel and natural polysaccharide sodium alginate, the problems of silicon-based negative electrode volume expansion and high complexity in the preparation of binder are solved, and efficient electrode stability is achieved and low-cost solutions.

CN119242212APending Publication Date: 2025-01-03SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411374649.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the prior art, the binder is difficult to effectively alleviate the volume expansion of the silicon-based negative electrode, and the preparation process of the binder is complex and costly.

Method used

Carboxymethylated tamarind polysaccharide gum and natural polysaccharide sodium alginate as binder compositions are used to generate a new binder with a three-dimensional network structure through the esterification reaction, which improves adhesion and dispersion between silicon particles and electrodes. reduces preparation costs.

Benefits of technology

It effectively alleviates the volume expansion of the silicon-based negative electrode, improves the mechanical strength and cycle stability of the electrode, simplifies the preparation process, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005068386680000071
    Figure BDA0005068386680000071
  • Figure BDA0005068386680000081
    Figure BDA0005068386680000081
Patent Text Reader

Abstract

The invention provides a binder composition, a binder, a preparation method of the binder and a negative plate. The binder composition comprises the following components in parts by weight: 1-8 parts of carboxymethylated tamarind polysaccharide gum, 1-4 parts of natural polysaccharide sodium alginate and 1-3 parts of a solvent. The carboxymethyl tamarind polysaccharide and the natural polysaccharide sodium alginate are subjected to simple esterification reaction to obtain a novel binder with a three-dimensional network structure, and the unique three-dimensional network structure can provide more acting sites with silicon particles, so that slippage is reduced, the integrity of an electrode is kept, and the service life of the electrode is prolonged. Therefore, the adhesion between the active material and the current collector is improved, the stability of the SEI film is promoted, and the mechanical strength of the pole piece is improved. Especially, when the composite material is applied to a silicon-based negative electrode, huge volume expansion of a silicon-based active material can be effectively relieved, so that the cycling stability of the silicon-based active material is improved. In addition, all the components are cheap and easy to obtain, so that the cost is relatively low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a binder composition, a binder and a preparation method thereof, and a negative electrode sheet. Background Art

[0002] With the growing demand for high energy density batteries, lithium-ion batteries with silicon-based materials as negative electrodes are constantly advancing. Because silicon has a high energy density of up to 4200mAh·g -1 Theoretical specific capacity, natural silicon resources are abundant, and silicon is environmentally friendly, so silicon has great potential as anode material. However, silicon will expand by 300% to 400% in repeated charge and discharge cycles, resulting in electrode structure collapse, conductive network damage, and continuous destruction and reconstruction of the SEI film, which in turn causes electrolyte loss and capacity loss, further limiting the electrochemical performance of silicon-based materials to a large extent and affecting their practical applications.

[0003] Generally, the binder mitigates the expansion of silicon particles by interacting with the surface of silicon particles, thereby ensuring the integrity of the electrode. A binder with good performance can evenly disperse the active material and the conductive agent in the solvent and effectively combine them together, so that they adhere evenly to the surface of the metal current collector.

[0004] Polymer binders play a vital role in improving the mechanical stability of electrodes. The traditional commercial binder polyvinylidene fluoride (PVDF) interacts with the surface of silicon particles through weak van der Waals forces, but it is not effective in limiting the expansion of silicon particles, and the preparation of electrode slurry requires the use of the dangerous, environmentally unfriendly and expensive organic solvent N-methylpyrrolidone (NMP). Water-based polymer binders can interact with the hydrophilic -Si-OH on the surface of silicon powder through -COOH, -OH, -NH2 and other hydrophilic groups to form hydrogen bonds or covalent bonds, thereby significantly enhancing the interfacial adhesion with silicon particles.

[0005] At present, several commonly used binders include SBR binder, PAA binder, natural polysaccharide binder and other three-dimensional cross-linked binders, but they are difficult to be promoted and applied because of their major defects, as follows:

[0006] 1) The SBR binder has a poor dispersion effect, and too much SBR binder will cause a large swelling problem; 2) The PAA binder has a linear structure. Due to the lack of sufficient contact points, when the silicon particles undergo repeated changes in volume during the electrochemical cycle, the long chains of the linear polymer binder will undergo irreversible slip and separation, and cannot maintain the integrity of the electrode during long-term cycles, so that the performance of the silicon-based negative electrode cannot be effectively improved; 3) The currently proposed natural polysaccharide binder has poor storage stability at room temperature; 4) The currently proposed three-dimensional cross-linked binders usually require a complex synthesis process and highly corrosive oxidants, which leads to high preparation costs and environmental unfriendliness. Summary of the invention

[0007] The main purpose of the present invention is to provide a binder composition, a binder and a preparation method thereof, and a negative electrode sheet to solve the problems in the prior art that the binder is difficult to effectively alleviate the volume expansion of the silicon-based negative electrode and the preparation process of the binder is complicated and costly.

[0008] To achieve the above object, according to one aspect of the present invention, a binder composition is provided, which comprises, by weight, 1 to 8 parts of carboxymethylated tamarind polysaccharide gum, 1 to 4 parts of natural polysaccharide sodium alginate and 1 to 3 parts of a solvent.

[0009] Furthermore, the mass ratio of the carboxymethylated tamarind polysaccharide gum to the natural polysaccharide sodium alginate is 6:(2-4).

[0010] Furthermore, the weight average molecular weight of the carboxymethylated tamarind polysaccharide gum is 600,000-1,300,000, preferably 800,000-1,000,000; and / or the weight average molecular weight of the natural polysaccharide sodium alginate is 500,000-2,000,000, preferably 800,000-1,200,000.

[0011] Furthermore, the solvent is selected from any one or more of water, ethanol and isopropanol. The preferred solvent is water, and further, preferably deionized water.

[0012] According to another aspect of the present invention, a method for preparing an adhesive is provided, the method comprising: step S1, stirring and mixing raw materials including carboxymethylated tamarind polysaccharide gum, natural polysaccharide sodium alginate and a solvent according to the raw material ratio in the above-mentioned adhesive composition to obtain a mixture; step S2, subjecting the mixture to an esterification reaction to obtain an adhesive.

[0013] Furthermore, the rotation speed of the stirring and mixing is 200 to 800 rpm, and / or the time of the stirring and mixing is 20 to 60 min.

[0014] Furthermore, the temperature of the esterification reaction is 60-80° C., and / or the time of the esterification reaction is 6-10 h.

[0015] According to another aspect of the present invention, there is provided an adhesive, which is prepared by the aforementioned preparation method.

[0016] Furthermore, the solid content of the above-mentioned binder is 4-10wt%, preferably 4-6wt%.

[0017] According to another aspect of the present invention, a negative electrode sheet is provided, which includes a negative electrode active material layer, the negative electrode active material layer includes a silicon-based negative electrode active material and the above-mentioned binder, preferably, the silicon-based negative electrode active material includes a silicon-carbon negative electrode active material.

[0018] Applying the technical solution of the present invention, the binder composition of the present application includes carboxymethylated tamarind polysaccharide gum, natural polysaccharide sodium alginate and solvent. Both carboxymethyl tamarind polysaccharide and natural polysaccharide sodium alginate are new green binders, which are very friendly to the environment, and both contain a large number of carboxyl and hydroxyl functional groups. Through a simple esterification reaction, a new binder with a three-dimensional network structure is obtained. Its unique three-dimensional network structure can provide more action sites with silicon particles, thereby reducing slippage, maintaining the integrity of the electrode, and then improving the adhesion between the active material and the current collector, promoting the stability of the SEI film, and improving the mechanical strength of the pole piece. At the same time, the new binder with a three-dimensional network structure improves the dispersion ability and room temperature storage stability of materials such as active materials, especially when applied to silicon-based negative electrodes, it can effectively alleviate the huge volume expansion of silicon-based active materials, thereby improving its cycle stability. In addition, the above components are cheap and easy to obtain, which makes the cost of this application low. DETAILED DESCRIPTION

[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0020] As analyzed in the background technology of the present application, in the prior art, silicon will undergo severe volume expansion during repeated charge and discharge cycles, resulting in collapse of the electrode structure, damage to the conductive network, continuous destruction and reconstruction of the SEI film, and electrolyte loss and capacity loss. That is, in the prior art, it is difficult for the binder to effectively alleviate the volume expansion of the silicon-based negative electrode, and the preparation process of the binder is complicated and the cost is high. In order to solve the above problems, the present application provides a binder composition, a binder and a preparation method thereof, and a negative electrode sheet.

[0021] In a typical embodiment of the present application, a binder composition is provided, which comprises, by weight, 1 to 8 parts of carboxymethylated tamarind polysaccharide gum, 1 to 4 parts of natural polysaccharide sodium alginate and 1 to 3 parts of a solvent.

[0022] The binder composition of the present application includes carboxymethylated tamarind polysaccharide gum, natural polysaccharide sodium alginate and solvent. Both carboxymethyl tamarind polysaccharide and natural polysaccharide sodium alginate are new green binders, which are very friendly to the environment, and both contain a large number of carboxyl and hydroxyl functional groups. Through a simple esterification reaction, a new binder with a three-dimensional network structure is obtained. Its unique three-dimensional network structure can provide more action sites with silicon particles, thereby reducing slippage, maintaining the integrity of the electrode, and then improving the adhesion between the active material and the current collector, promoting the stability of the SEI film, and improving the mechanical strength of the pole piece. At the same time, the new binder with a three-dimensional network structure improves the dispersion ability and room temperature storage stability of materials such as active materials, especially when applied to silicon-based negative electrodes, it can effectively alleviate the huge volume expansion of silicon-based active materials, thereby improving their cycle stability. In addition, the above components are cheap and easy to obtain, which makes the cost of this application low.

[0023] In one embodiment of the present application, the mass ratio of the above-mentioned carboxymethylated tamarind polysaccharide gum to the natural polysaccharide sodium alginate is 6:(2-4).

[0024] If the content of natural polysaccharide sodium alginate is too high, the stability of the electrode slurry prepared therefrom will be reduced, and the viscosity retention rate will be reduced, so that the slurry is easy to settle, affecting the subsequent coating performance, and then the processing performance of the electrode sheet will deteriorate. If the content of natural polysaccharide sodium alginate is too low, the bonding force of the obtained binder is poor. Therefore, it is preferred to control the mass ratio of carboxymethylated tamarind polysaccharide gum to natural polysaccharide sodium alginate within the above range, which helps to promote the sufficiency of the reaction between the hydroxyl and carboxyl groups in carboxymethylated tamarind polysaccharide gum and natural polysaccharide sodium alginate, thereby making the three-dimensional network structure of the esterification product more stable, thereby improving the bonding force of the binder and further improving the stability of the electrode slurry.

[0025] In one embodiment of the present application, the weight average molecular weight of the carboxymethylated tamarind polysaccharide gum is 600,000-1,300,000, preferably 800,000-1,000,000; and / or the weight average molecular weight of the natural polysaccharide sodium alginate is 500,000-2,000,000, preferably 800,000-1,200,000.

[0026] It is preferred to control the weight average molecular weights of the carboxymethylated tamarind polysaccharide gum and the natural polysaccharide sodium alginate respectively within the above ranges, thereby facilitating further control of the adhesive force of the three-dimensional network structure adhesive.

[0027] The binder obtained by esterification of carboxymethylated tamarind polysaccharide gum with natural polysaccharide sodium alginate is a water-soluble binder. Therefore, in order to improve the dispersion uniformity of each component in the binder composition, thereby smoothly forming a uniform slurry and controlling its viscosity as much as possible, the above-mentioned solvent is preferably any one or more of water, ethanol and isopropanol, and the solvent is preferably water, and further, preferably deionized water. In addition, due to the low conductivity of deionized water, it helps to reduce the electrochemical corrosion of the binder during the application process; on the other hand, since deionized water contains almost no impurities, the influence of impurities in the solvent on the performance of the binder can be avoided.

[0028] In another typical embodiment of the present application, a method for preparing an adhesive is provided, the method comprising: step S1, stirring and mixing raw materials including carboxymethylated tamarind polysaccharide gum, natural polysaccharide sodium alginate and a solvent according to the raw material ratio in the aforementioned adhesive composition to obtain a mixture; step S2, subjecting the mixture to an esterification reaction to obtain an adhesive.

[0029] In the present application, carboxymethylated tamarind polysaccharide gum and natural polysaccharide sodium alginate are first uniformly dispersed in a solvent, thereby increasing the contact area between carboxymethylated tamarind polysaccharide gum and natural polysaccharide sodium alginate, thereby improving the efficiency and effect of the esterification reaction of the two. The carboxymethylated tamarind polysaccharide and natural polysaccharide sodium alginate of the present application are both new green binders, and the new binders obtained by the esterification reaction have a three-dimensional network structure, and their unique three-dimensional network structure can provide more action sites with silicon particles, thereby reducing slippage, maintaining the integrity of the electrode, and then improving the adhesion between the active material and the current collector, promoting the stability of the SEI film, and improving the mechanical strength of the pole piece. At the same time, the new binder with a three-dimensional network structure improves the dispersion ability and room temperature storage stability of materials such as active materials, especially when applied to silicon-based negative electrodes, it can effectively alleviate the huge volume expansion of silicon-based active materials, thereby improving their cycle stability. In addition, the above components are cheap and easy to obtain, and the synthesis process is simple, thereby greatly reducing the cost of the binder.

[0030] In one embodiment of the present application, the rotation speed of the stirring and mixing is 200 to 800 rpm, and / or the stirring and mixing time is 20 to 60 min.

[0031] The above preferred stirring conditions are helpful to improve the dispersibility of carboxymethylated tamarind polysaccharide gum and natural polysaccharide sodium alginate in the solvent.

[0032] In order to make the esterification reaction of carboxymethylated tamarind polysaccharide gum and natural polysaccharide sodium alginate more complete, in one embodiment of the present application, the temperature of the esterification reaction is preferably 60-80° C., and / or the time of the esterification reaction is 6-10 h.

[0033] In some embodiments of the present application, the above preparation method also includes a method for preparing carboxymethylated tamarind polysaccharide gum:

[0034] The natural tamarind gum powder is subjected to substitution reaction with a halogenated monosubstituted acid in an alkaline solution to obtain carboxymethylated tamarind polysaccharide gum.

[0035] Wherein, the alkaline solution comprises an alkali and an alcohol solvent, wherein the alkali is sodium hydroxide and / or potassium hydroxide; the alcohol solvent is preferably isopropanol and / or ethanol, preferably isopropanol, on the one hand, since isopropanol is a polar solvent, it can dissolve a variety of organic substances, on the other hand, since isopropanol has a lower boiling point, it can volatilize quickly in the air. Preferably, the above-mentioned halogenated monosubstituted acid is selected from any one or more of monochloroacetic acid, monobromoacetic acid, chloropropionic acid and bromopropionic acid. Since monochloroacetic acid contains active chlorine atoms, it is preferred that the halogenated monosubstituted acid is monochloroacetic acid, which is more conducive to improving the reaction activity of the substitution reaction.

[0036] In another typical embodiment of the present application, the above-mentioned binder is prepared by the aforementioned preparation method.

[0037] The present application is a novel binder obtained by esterification reaction of carboxymethylated tamarind polysaccharide gum with natural polysaccharide sodium alginate, which has a three-dimensional network structure. Since the binder has a unique three-dimensional network structure, it can not only ensure the integrity of the electrode during the electrochemical cycle; but also make its binding force with silicon stronger, so that the silicon-based negative electrode sheet can adapt to the volume change of silicon during the charge and discharge cycle, which is conducive to the long-term and high-rate rapid charge and discharge of the silicon-based negative electrode. At the same time, the viscosity retention rate of the three-dimensional network binder is high, the dispersibility of active substances and conductive agents is good, the electron transfer rate is increased, and the cycle performance of the silicon-based negative electrode of the lithium-ion battery is improved.

[0038] In one embodiment of the present application, the solid content of the above-mentioned binder is 4-10wt%, preferably 4-6wt%.

[0039] It is preferred to control the solid content of the binder within the above range, which helps to improve the coatability of the slurry coating process and is beneficial to improving the bonding strength of the binder.

[0040] In another typical embodiment of the present application, a negative electrode sheet is provided, which includes a negative electrode active material layer, the negative electrode active material layer includes a silicon-based negative electrode active material and the above-mentioned binder, preferably, the silicon-based negative electrode active material includes a silicon-carbon negative electrode active material.

[0041] The silicon negative electrode sheet including the binder of the present application has high mechanical stability and maintains the integrity of the electrode during long-term cycles, thereby improving the cycle performance of the silicon-based negative electrode of the lithium-ion battery.

[0042] Preferably, the preparation method of the above-mentioned negative electrode sheet comprises: applying the negative electrode slurry to the negative electrode current collector and then drying and laminating to obtain the negative electrode sheet, wherein the negative electrode slurry comprises a silicon-based negative electrode active material, a conductive agent and a binder, and the binder is the aforementioned binder.

[0043] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0044] Example 1

[0045] 10g natural tamarind gum powder is slowly added into the three-necked flask equipped with 200g isopropanol solvent, placed in a thermostatic water bath, temperature is 25 ℃, with N2 as protective gas, open magnetic stirrer and stir for 30min, the rotating speed of magnetic stirrer is 200rpm. Then slowly add 100mL 0.375mol / L sodium hydroxide solution and stir for 30min (stirring speed is 300rpm), then, 1.8g monochloroacetic acid is dissolved in the beaker equipped with 100g isopropanol solvent, divided into three times and added into the three-necked flask, after adding, placed in a thermostatic water bath, temperature is 25 ℃, with N2 as protective gas, open magnetic stirrer and stir for 8h (stirring speed is 200rpm), obtain crude reaction product after filtration, use 500mL absolute ethanol to wash the crude reaction product 3 times, thereby remove impurity, after suction filtration, solid is freeze-dried for 15h, obtain carboxymethylated tamarind polysaccharide gum powder.

[0046] In a constant temperature water bath at 25°C, 2g of natural polysaccharide sodium alginate powder (weight average molecular weight of 800,000) was slowly added into a beaker containing 100g of deionized water and stirred to completely dissolve. Subsequently, 6g of prepared carboxymethyl tamarind polysaccharide powder (weight average molecular weight of 1,000,000) was slowly added to make the mass ratio of carboxymethyl tamarind polysaccharide gum to natural polysaccharide sodium alginate 6:2. The mixture was magnetically stirred at 25°C for 40min at a speed of 300rpm to completely dissolve the mixture. The reaction system was stirred at 80°C for 10 hours to allow the two to fully undergo esterification reaction to obtain a binder.

[0047] Example 2

[0048] The difference from Example 1 is that 3 g of the prepared carboxymethyl tamarind polysaccharide powder is slowly added to make the mass ratio of carboxymethyl tamarind polysaccharide gum to natural polysaccharide sodium alginate be 6:4, and finally a binder is obtained.

[0049] Example 3

[0050] The difference from Example 1 is that 4 g of the prepared carboxymethyl tamarind polysaccharide powder is slowly added to make the mass ratio of carboxymethyl tamarind polysaccharide gum to natural polysaccharide sodium alginate be 6:3, and finally a binder is obtained.

[0051] Example 4

[0052] The difference from Example 1 is that 12 g of the prepared carboxymethyl tamarind polysaccharide powder is slowly added to make the mass ratio of carboxymethyl tamarind polysaccharide gum to natural polysaccharide sodium alginate be 6:1, and finally a binder is obtained.

[0053] Example 5

[0054] The difference from Example 1 is that the weight average molecular weight of the carboxymethylated tamarind polysaccharide gum is 800,000, and a binder is finally obtained.

[0055] Example 6

[0056] The difference from Example 1 is that the weight average molecular weight of the carboxymethylated tamarind polysaccharide gum is 600,000, and a binder is finally obtained.

[0057] Example 7

[0058] The difference from Example 1 is that the weight average molecular weight of the carboxymethylated tamarind polysaccharide gum is 1,300,000, and a binder is finally obtained.

[0059] Example 8

[0060] The difference from Example 1 is that the weight average molecular weight of the natural polysaccharide sodium alginate is 1,200,000, and a binder is finally obtained.

[0061] Example 9

[0062] The difference from Example 1 is that the weight average molecular weight of the natural polysaccharide sodium alginate is 2,000,000, and a binder is finally obtained.

[0063] Example 10

[0064] The difference from Example 1 is that the weight average molecular weight of the natural polysaccharide sodium alginate is 500,000, and a binder is finally obtained.

[0065] Embodiment 11

[0066] The difference from Example 1 is that after the prepared carboxymethyl tamarind polysaccharide powder is added, the speed of the magnetic stirrer is 800 rpm, and the magnetic stirring mixing time is 60 minutes, and finally a binder is obtained.

[0067] Example 12

[0068] The difference from Example 1 is that the temperature for the esterification reaction between the carboxymethylated tamarind polysaccharide gum and the natural polysaccharide sodium alginate is 60° C. and the reaction time is 8 hours to finally obtain the adhesive.

[0069] Comparative Example 1

[0070] The difference from Example 1 is that only sodium carboxymethyl cellulose is selected as the binder.

[0071] Comparative Example 2

[0072] The difference from Example 1 is that only polyacrylic acid is selected as the binder.

[0073] Comparative Example 3

[0074] The difference from Example 1 is that only carboxymethylated tamarind polysaccharide gum is selected as the binder.

[0075] Comparative Example 4

[0076] The difference from Example 1 is that only natural polysaccharide sodium alginate is selected as the binder.

[0077] Performance Testing

[0078] Take the binders of the above-mentioned embodiment and comparative example respectively, and mix the silicon-carbon active material, conductive carbon black and binder in a mass ratio of 8:1:1, grind them thoroughly, add N-methylpyrrolidone, stir them at a speed of 3000 r / min for 2 h until they are uniformly mixed, and prepare a paste-like negative electrode slurry with a viscosity of 200 mPa·S; use a scraper to evenly scrape the slurry on a copper foil to obtain a current collector coated with the electrode slurry, place the current collector coated with the electrode slurry in a vacuum and dry it at 60°C, and then roll the slurry coated on the current collector to obtain a silicon-carbon negative electrode sheet.

[0079] The above silicon-carbon negative electrode sheet and lithium sheet were used as the negative electrode and positive electrode of the lithium-ion battery respectively, Celgard 2400 was used as the separator, and a mixed solution of 1 mol / L LiPF6 of EC and EMC (v / v=1:1) was used as the electrolyte solution. The button cells were assembled for charge and discharge tests. The specific test results are shown in Table 1.

[0080] At 100mA·g -1 The charge and discharge test was carried out at a charge and discharge current density of 1.5 g. The test results are shown in Table 1.

[0081] Table 1

[0082]

[0083]

[0084] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0085] The binder composition of the present application includes carboxymethylated tamarind polysaccharide gum, natural polysaccharide sodium alginate and solvent. Both carboxymethyl tamarind polysaccharide and natural polysaccharide sodium alginate are new green binders, which are very friendly to the environment, and both contain a large number of carboxyl and hydroxyl functional groups. Through a simple esterification reaction, a new binder with a three-dimensional network structure is obtained. Its unique three-dimensional network structure can provide more action sites with silicon particles, thereby reducing slippage, maintaining the integrity of the electrode, and then improving the adhesion between the active material and the current collector, promoting the stability of the SEI film, and improving the mechanical strength of the pole piece. At the same time, the new binder with a three-dimensional network structure improves the dispersion ability and room temperature storage stability of materials such as active materials, especially when applied to silicon-based negative electrodes, it can effectively alleviate the huge volume expansion of silicon-based active materials, thereby improving their cycle stability. In addition, the above components are cheap and easy to obtain, which makes the cost of this application low.

[0086] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A binder composition, characterized in that: In parts by weight, the binder composition comprises: 1 to 8 parts of carboxymethylated tamarind polysaccharide gum; 1 to 4 parts of natural polysaccharide sodium alginate; 1 to 3 parts of solvent.

2. The adhesive composition according to claim 1, characterized in that The mass ratio of the carboxymethylated tamarind polysaccharide gum to the natural polysaccharide sodium alginate is 6:(2-4).

3. The adhesive composition according to claim 1 or 2, characterized in that: The weight average molecular weight of the carboxymethylated tamarind polysaccharide gum is 600,000-1,300,000, preferably 800,000-1,000,000; and / or the weight average molecular weight of the natural polysaccharide sodium alginate is 500,000-2,000,000, preferably 800,000-1,200,000.

4. The adhesive composition according to any one of claims 1 to 3, characterized in that The solvent is selected from any one or more of water, ethanol and isopropanol. Preferably, the solvent is water, and further preferably, deionized water.

5. A method for preparing a binder, characterized in that: The preparation method comprises: Step S1, stirring and mixing raw materials including carboxymethylated tamarind polysaccharide gum, natural polysaccharide sodium alginate and a solvent according to the raw material ratio in the adhesive composition of any one of claims 1 to 4 to obtain a mixture; Step S2, subjecting the mixture to an esterification reaction to obtain a binder.

6. The preparation method according to claim 5, characterized in that: The stirring and mixing speed is 200 to 800 rpm, and / or the stirring and mixing time is 20 to 60 min.

7. The preparation method according to claim 5 or 6, characterized in that: The temperature of the esterification reaction is 60-80° C., and / or the time of the esterification reaction is 6-10 hours.

8. A binder, characterized in that: The binder is prepared by the preparation method according to any one of claims 5 to 7.

9. The adhesive according to claim 8, characterized in that The solid content of the binder is 4-10 wt %, preferably 4-6 wt %.

10. A negative electrode sheet, comprising a negative electrode active material layer, characterized in that: The negative electrode active material layer comprises a silicon-based negative electrode active material and the binder according to claim 8 or 9. Preferably, the silicon-based negative electrode active material comprises a silicon-carbon negative electrode active material.